2011
DOI: 10.1007/s10059-011-1009-3
|View full text |Cite
|
Sign up to set email alerts
|

Modified Apolipoprotein (apo) A-I by Artificial Sweetener Causes Severe Premature Cellular Senescence and Atherosclerosis with Impairment of Functional and Structural Properties of apoA-I in Lipid-Free and Lipid-Bound State

Abstract: Long-term consumption of artificial sweeteners (AS) has been the recent focus of safety concerns. However, the potential risk of the AS in cardiovascular disease and lipoprotein metabolism has not been investigated sufficiently. We compared the influence of AS (aspartame, acesulfame K, and saccharin) and fructose in terms of functional and structural correlations of apolipoprotein (apo) A-I and high-density lipoproteins (HDL), which have atheroprotective effects. Long-term treatment of apoA-I with the sweetene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Thus, we have described, for the fi rst time, the increase of a 26 kDa N-terminal truncated form of ApoA-I that we have named ApoA-I ⌬ (1-38) that associates to the denser LDL particles in DM patients which may have effects in lipoprotein particle turnover, increase LDL susceptibility to oxidation, and further contribute to a higher cardiovascular risk. The presence of cleaved ApoA-I variants is closely related to the incidence of chronic diseases such as diabetes, atherosclerosis, and ageing ( 55 ). Therefore the potential role of this truncated Supplemental Material can be found at:…”
Section: Cathepsin D-cleaved Apoa-i Exhibits Increased Ldl Binding Abmentioning
confidence: 99%
“…Thus, we have described, for the fi rst time, the increase of a 26 kDa N-terminal truncated form of ApoA-I that we have named ApoA-I ⌬ (1-38) that associates to the denser LDL particles in DM patients which may have effects in lipoprotein particle turnover, increase LDL susceptibility to oxidation, and further contribute to a higher cardiovascular risk. The presence of cleaved ApoA-I variants is closely related to the incidence of chronic diseases such as diabetes, atherosclerosis, and ageing ( 55 ). Therefore the potential role of this truncated Supplemental Material can be found at:…”
Section: Cathepsin D-cleaved Apoa-i Exhibits Increased Ldl Binding Abmentioning
confidence: 99%
“…Another study showed that treatment of apolipoproteinA-1 and HDL with 3mM of saccharin or aspartame for 16h resulted in the loss of their antioxidant and phospholipid binding activities, and accelerated the senescence of human dermal fibroblasts [29]. High artificial sweeteners intake was shown to be associated with increased BMI and body fat percentage in males and females [22,67].…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerotic apolipoprotein E-deficient (apoE-/-) mice, consumption of aspartame-acesulfame K sweetened 'light' cola was found to accelerate the progression of atherosclerotic plaques and the accumulation of sub-endothelial lipid-laden macrophages [27,28]. Also, in vitro treatment of apoA-I or HDL with physiological concentrations of aspartame, acesulfame K, or saccharin resulted in their pro-oxidative and pro-atherogenic modifications [29,30]. On the other hand, consumption of stevioside by leptin and LDLR double knockout mice was reported to reduce the aortic plaque volume by decreasing the content of macrophages, lipids, and ox-LDL in the plaque [31].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, we compared the functional and structural effects of AS on apolipoprotein A-I (apoA-I), which is a major protein component of high-density lipoprotein (HDL). Among the various AS, saccharin induced the most severe impairment of apoA-I in addition to pro-senescence activity [3]. However, aspartame-fed hypercholesterolemic zebrafish display acute death with swimming defects, suggesting putative brain damage induced by aspartame [4].…”
Section: Introductionmentioning
confidence: 98%
“…We have previously reported that the properties of both apoA-I and rHDL are impaired by fructosylation [7] or AS treatment [3]. However, it remains unknown whether or not the properties of human plasma HDL are affected by treatment with fructose or AS.…”
Section: Introductionmentioning
confidence: 99%